Dal De viris illustribus al De mulieribus claris - Sciacovelli, Antonio Donato (Verbum – Analecta Neolatina, 2005)
The present article shows the affinities in some biographical writings of Francesco Petrarca and Giovanni Boccaccio: the theme of the exaltation of the past, as opposed to the present time, as well as the corruption of the modern man may well be the very fundamental trait d'union between the two writers.